Hearing glasses to visually impaired people prototype - Viti, Vinícius Mafra; Marques, Bruno Augusto Dorta (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20032, 2021)
This research aims to study the feasibility of glasses with a camera as a guide for the visually impaired. This idea will be developed to provide these people a way to "see, feel, and experience" the world in a different way. Thus, the development of such technology will be done employing Artificial Intelligence and Computer Vision resources/software. Some attention is given to visually impaired people, although many still experience great difficulty getting around and living alone, directly impacting their quality of life. Hence, implementing the proposed idea is extremely necessary since it will bring a sense of the environment to those who cannot visualize it and suffer daily. Therefore, the research will consist of conducting an improved study on the best methodology and technology to identify objects in front of blind people. The objective is to identify the most relevant objects, providing distance cues to the visually impaired person.